Paul Soldner thrown and altered clay : a retrospective. - Crystal Productions (Aspen, Colo. : Crystal Productions, 1992)
This program traces the evolution of Soldner's work over forty years from functional thrown stoneware to his nonfunctional raku sculptured forms and cast bronze pieces.
VHS format.
Keywords: Soldner, Paul; Ceramic sculpture -- United States